The Relationship Between Work-Life Balance and Job Satisfaction Among Remote Workers (Proceeding of The International Conference on Economics and Business, 2024)
Remote work has gained prominence in the modern workplace, raising concerns about work-life balance. This study investigates the relationship between work-life balance and job satisfaction among remote workers. Survey data from 500 respondents reveal that flexibility and time management significantly influence job satisfaction, providing insights for remote work policies.